Anorectal Malformations Associated with Hirschsprung Disease: Insights from a Large Cohort of 2,341 ARM Patients in a Single-Center Retrospective Study - Xiao, Xianming; Feng, Wei; Zhu, Jin; Fan, Linxiao; Xiang, Chenzhu; Wang, Zhili; Hou, Jinping; Liu, Wei; Guo, Zhenhua; Wang, Yi (European Journal of Pediatric Surgery, 2025)
Anorectal malformation (ARM) and Hirschsprung disease (HSCR) are common congenital gastrointestinal defects, but their co-occurrence is rare. This retrospective study analyzed the clinical characteristics of patients with ARM associated with HSCR for early diagnosis and treatment guidance to reduce the occurrence of severe complications.A single-center retrospective cohort analysis from 2010 to 2024 identified 2,341 patients with ARM and 1,721 with HSCR. The histopathologic assessment included hematoxylin and eosin (H&E) staining and immunohistochemical staining.Seven patients (0.3%) out of 2,341 cases of ARM were diagnosed with concurrent HSCR, three males (42.9%) and four females (57.1%). Seven cases are rectoperineal fistula. All cases developed constipation with abdominal distension within 1 month to 1 year after anoplasty, even following aggressive bowel management. Barium enema showed obvious transition zones, and anorectal manometry revealed absent rectoanal inhibitory reflex in seven cases. All patients underwent the Swenson procedure. The mean duration of postoperative follow-up was 7.5 ± 2.8 years. Seven cases had no constipation, no soiling, voluntary bowel movements by Krickenbeck classification, and excellent continence by the Rintala scoring system in recent follow-up.The association between ARM and HSCR may be rarer than previously reported. Low-type ARM and short or rectosigmoid aganglionosis appeared more common in these cases. Persistent postoperative constipation and abdominal distension unresponsive to conservative treatment should raise suspicion for HSCR, prompting timely diagnostic evaluations. Postoperative bowel function needs to be interpreted carefully, and prospective studies are needed to confirm these findings and guide standardized care.
Keywords: anorectal malformation; Hirschsprung's disease; histopathological assessment; barium enema; anaorectal manometry